Perubahan Undang Undang Dasar : Pemahaman Tentang Arti Perubahan, Tata Cara Perubahan, Kajian Kritis Terhadap Amandemen UUD 1945 - Fitri Natasha Dachi; Wilma Silalahi (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
The amendment of the 1945 Constitution of Indonesia is a crucial legal and political mechanism within the dynamics of constitutional law. An amendment is understood as an adjustment of constitutional norms to remain relevant with changing times while preserving the state’s fundamental identity. Unlike a constitutional replacement, which is comprehensive and signifies the birth of a new constitutional order, amendments are partial and limited. Article 37 of the 1945 Constitution sets out strict procedures, including requirements for proposal, quorum, and substantive limitations that cannot be altered, namely the form of the Unitary State of the Republic of Indonesia. This mechanism prevents arbitrary changes and safeguards legal and political stability. The 1999–2002 amendments demonstrate that the Constitution can be improved without disrupting national continuity. Therefore, amendments are viewed as an evolutionary form of constitutional reform, while replacement signifies radical change. This analysis highlights that the amendment procedure of the 1945 Constitution is designed to balance the need for flexibility with constitutional stability in Indonesia.